Motivations and Experiences of Teachers in a Northern Manitoba Community - Janzen, Melanie D.; Cranston, Jerome (Alberta Journal of Educational Research, 2016)
This paper utilizes an exploratory case study method to examine the factors that attract and motivate teachers to stay in a remote, northern Canadian community. Bakan’s (1966) framework of agency and communion, provides a lens for exploring and understanding teachers’ experiences of working in the north where the term “the North” is understood not simply as one of two geographical poles, but also represents a consciousness of place. Subsequently, this study expands the conceptualization of Bakan’s notion of communion to include both the effects of emotion, which can be understood specifically as public, social, and in relation to others; as well as socio-spatial factors that illustrate the ways in which space is conceived, perceived and lived. Given the amount of human and financial capital required to recruit and retain teachers, as well as the negative implications that high levels of teacher attrition have on student success and emotional well-being, it is important to understand teachers’ perspectives on their experiences working in communities that are perceived as hard to staff. Cet article adopte une méthodologie exploratoire reposant sur l’étude de cas pour examiner les facteurs qui attirent les enseignants vers une communauté isolée du Nord canadien, et les motivent à y rester. Le cadre de l’agentivité et de la communion de Bakan (1966) offre une perspective à partir de laquelle explorer et comprendre les expériences des enseignants qui travaillent dans le nord, où l’expression « le nord » ne désigne pas uniquement un des deux pôles géographiques, mais aussi la conscience d’un lieu. Par la suite, l’étude étend la conceptualisation de la notion de communion de Bakan pour inclure les effets de l’émotion (que l’on comprend comme étant publiques, sociales et par rapport aux autres) ainsi que les facteurs socio-spatiaux qui illustrent les façons dont les lieux sont conçus, perçus et vécus. Compte tenu du capital humain et financier nécessaire pour recruter les enseignants et les maintenir en poste, ainsi que des incidences négatives qu’a le taux élevé de départ volontaire des enseignants sur le rendement et le bienêtre émotionnel des élèves, il est important de comprendre les perspectives des enseignants sur leurs expériences de travail dans des communautés perçues comme étant difficiles à pourvoir en personnel.